High resolution space based wind observations estimation and application – A Review - MARSHALL, J. LE; LESLIE, L. M.; SEECAMP, R.; REA, A. (MAUSAM, 2003)
As the spatial, temporal and spectral resolution of visible and infrared radiance observations from space has improved, their utility for estimating atmospheric motion, and, in particular, their benefit to Numerical Weather Prediction (NWP) has increased. The utility of these data has also been aided by increased computer power, improved NWP models and the use of improving data assimilation techniques. This review provides a brief history of the generation and application of Atmospheric Motion Vectors (AMVs), including a short description of high spatial and temporal resolution AMV processing. All AMV data types are both suitable and now used for operational regional and global NWP and the data selection and quality control issues important to NWP are discussed. A brief examination of preparations for future advanced instruments is also undertaken.